Kelapa dalam Catatan Arkeologi dan Historis: Upaya Pengembangan Kebijakan Tanaman Serba Guna - Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2013)
AbstractHistorical and archaeological sources in this article suggest the Indonesia's coconuts cultivation and varied uses of the tree parts, such as their flowers which produce sap (an ingredient of brown sugar and fermented palm wine), leaves for fish traps/breeding place, roofing materials, and banners. Copras, the main ingredient of oil making, butter, and soap, which are acquired from the coconut flesh, were used to be a worldwide export commodity in Indonesian pre-independence period. Once was only processed into copras, coconut flesh has now product varieties. Nowadays, the demand for coconut has soared but the production ironically is declining. As a matter of fact, Indonesia's coconut plantation is actually the largest in size in the world, yet the products are unfortunately not well-organized as strategic commodity. Furthermore, the plant production is so low that the supply suffers from it. The government seems to focus only on coconut palms, which is ironic due to the horrible environmental damaging effect caused by the exploitative land clearing for the plantations. Coconut palm plantations are mostly owned by rich business people, while the coconuts plantations belong to common people. Most of the people's coconut plantations have old and unproductive trees, which need replanting for the sake of the people welfare improvement.AbstrakSumber sejarah dan arkeologi yang diolah dalam artikel ini memperlihatkan masyarakat Indonesia sudah lama membudidayakan tanaman kelapa dan memanfaatkan berbagai bagian pohonnya. Diantaranya bunga kelapa yang menghasilkan nira (bahan baku gula merah dan tuak), daun kelapa dijadikan rumpon, atap, dan umbul-umbul. Kopra - bahan utama pembuatan minyak, mentega, dan sabun - diperoleh dari daging kelapa, dan sebelum Indonesia merdeka merupakan komoditas ekspor yang mendunia. Dahulu daging kelapa hanya diolah menjadi kopra, saat ini variasi produknya semakin beragam. Kebutuhan kelapa menjadi sangat tinggi, namun produksi kelapa malah cenderung berkurang. Areal tanaman kelapa Indonesia terluas di dunia, namun belum terkelola sebagai komoditas strategis. Produksi tanamannya rendah sehingga pasokan kelapa tidak maksimal. Pemerintah cenderung berfokus pada kelapa sawit, sementara diketahui bahwa perkebunan kelapa sawit yang belakangan banyak dibuka secara besar-besaran ditengarai memunculkan dampak lingkungan yang besar. Bila perkebunan kelapa sawit banyak dimiliki pengusaha kaya, sebagian besar perkebunan kelapa adalah milik rakyat. Sebagian besar perkebunan rakyat itu tanamannya tua dan tidak produktif lagi, sehingga peremajaan tanaman kelapa harus dilakukan bagi peningkatan kesejahteraan masyarakat.